The Development of Surface Electromyography Signal Acquisition and Processing Method for Muscle Fatigue Evaluation - Widodo Saputra - Nim: 13114107 , Aldo
Development in diagnosis and treatment has improved human health. A particular technological advancement in diagnosis is the invention of surface electromyography (sEMG). The risk factor of sEMG is lower than the conventional electromyography (EMG). Due to its low risk and ease of use, sEMG popularity has grown fast. Typical application of sEMG is in muscle fatigue evaluation. In this research, muscle fatigue evaluation is developed based on sEMG signal measurement. As a preliminary step, frequency domain method is employed. In this case, the method evaluates mean and median frequencies of the power spectral density (PSD). sEMG measurement was executed to one individual and in one particular location, i.e., biceps, since the objective is to develop the correct procedure, along with the development of the signal processing tools and programs to calculate the mean and median frequencies. sEMG signals are measured in isometric contraction case, i.e., the case in which the muscle fiber length remains constant. The above procedure follows common rules set by the sEMG community. After performing sEMG signal measurements and analysis, decrease in mean and median frequencies for isometric contractions are observed. The above phenomenon is similar to other research results. As a future work, the developed procedure will be implemented in measuring several individuals, before a novel alternative diagnosis tool other than mean and median frequencies may be proposed.